2007
DOI: 10.1099/vir.0.82419-0
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus NS1 protein activates the phosphatidylinositol 3-kinase (PI3K)/Akt pathway by direct interaction with the p85 subunit of PI3K

Abstract: Influenza A virus infection activates the phosphatidylinositol 3-kinase (PI3K)/Akt pathway, but the mechanism is not clear. Here, it is reported that influenza A virus NS1 protein is responsible for PI3K/Akt pathway activation. It was demonstrated that the NS1 protein interacts with the p85 regulatory subunit of PI3K via direct binding to the SH3 and C-terminal SH2 domains of p85. Consensus binding motifs for SH3 and SH2 domains were found in influenza A virus NS1, namely an SH2-binding motif (YXXXM) at aa 89,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
164
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(171 citation statements)
references
References 26 publications
(24 reference statements)
7
164
0
Order By: Relevance
“…The NS1 protein has been reported to have multiple functions including controlling the temporal synthesis of viral-specific mRNA and viral genomic RNAs (12,13) and interacting with the cellular protein phosphatidylinositol-3-kinase (PI3-kinase) (14)(15)(16), which may cause a delay in virus-induced apoptosis (17). However, the majority of previous work has focused on the ability of NS1 to circumvent the host cell antiviral responses.…”
mentioning
confidence: 99%
“…The NS1 protein has been reported to have multiple functions including controlling the temporal synthesis of viral-specific mRNA and viral genomic RNAs (12,13) and interacting with the cellular protein phosphatidylinositol-3-kinase (PI3-kinase) (14)(15)(16), which may cause a delay in virus-induced apoptosis (17). However, the majority of previous work has focused on the ability of NS1 to circumvent the host cell antiviral responses.…”
mentioning
confidence: 99%
“…By identifying the replication defect of a recombinant influenza A/Udorn/72 (Ud) virus that encodes an NS1A protein lacking dsRNA-binding activity, it was established that the primary role of NS1A dsRNA-binding activity is the inhibition of the IFN-␣/␤-induced oligo A synthetase/RNase L pathway, and that NS1A dsRNA-binding activity has no detectable role in inhibiting the production of IFN-␤ mRNA or inhibiting the activation of protein kinase R (PKR) (4,5). The rest of the NS1A protein, which is referred to as the effector domain, has binding sites for several cellular proteins, including: the cellular 30-kDa subunit of the cleavage and polyadenylation specificity factor (CPSF30), a cellular factor required for the 3Ј end processing of cellular pre-mRNAs, thereby inhibiting the production of all cellular mRNAs, including IFN-␤ mRNA (6-10); p85␤, resulting in the activation of phosphatidylinositol-3-kinase signaling (11)(12)(13)(14); and PKR, resulting in the inhibition of PKR activation (15).…”
mentioning
confidence: 99%
“…Most importantly, a number of studies have shown that influenza virus can effectively activate the MAPK pathways and the activation of MAPK family members plays an important role in viral replication, proinflammatory and apoptotic response in various cells during influenza virus infection [6974]. Moreover, the PI3K/Akt/mTOR pathway also activated during influenza virus infection and function as supporting viral effective replication [7580]. …”
Section: Discussionmentioning
confidence: 99%